Formation of Relational Strategy as Economic Security Factor of t Nuclear Industry Enterprises (on the Example of Machine-Building Enterprises in Volgodonsk) - Golovko, M. V.; Setrakov, A. N.; Rogacheva, J. S.; Antsibor, A. V. (Глобальная ядерная безопасность, 2022)
The paper discusses the benefits of developing and implementing a relational strategy in industrial enterprises. The authors interpret the report as «co-competition» necessary in modern conditions. This makes it possible to achieve long-term benefits both for economic entities experiencing a shortage of any type of resources, and for those who hold a fairly stable position in the market. Some results of approbation of the author's methodology are presented on the example of enterprises in Volgodonsk that manufacture products for the power engineering industry but are not part of the «Rosatom» State Corporation.